2019
DOI: 10.1053/j.gastro.2019.07.036
|View full text |Cite
|
Sign up to set email alerts
|

ECM1 Prevents Activation of Transforming Growth Factor β, Hepatic Stellate Cells, and Fibrogenesis in Mice

Abstract: BACKGROUND & AIMS: Activation of TGFB (transforming growth factor b) promotes liver fibrosis by activating hepatic stellate cells (HSCs), but the mechanisms of TGFB activation are not clear. We investigated the role of ECM1 (extracellular matrix protein 1), which interacts with extracellular and structural proteins, in TGFB activation in mouse livers. METHODS:We performed studies with C57BL/6J mice (controls), ECM1-knockout (ECM1-KO) mice, and mice with hepatocyte-specific knockout of EMC1 (ECM1 Dhep ). ECM1 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 38 publications
5
79
2
Order By: Relevance
“…They hypothesized that this increase in ECM1 protein expression levels results in higher rigidity in the adipose tissue, promoting fibrosis. This hypothesis is supported by a recent study by Fan et al, who demonstrated that high expression levels of ECM1 inhibit transforming growth factor beta (TGFB) activation to prevent liver fibrosis (32). Lee et al investigated the functional role of ECM1 and concluded that it interacts with the epidermal growth factor (EGF) domain of various proteins, including HSPG2, and induce heparin-binding growth factor responses (33).…”
Section: Discussionmentioning
confidence: 92%
“…They hypothesized that this increase in ECM1 protein expression levels results in higher rigidity in the adipose tissue, promoting fibrosis. This hypothesis is supported by a recent study by Fan et al, who demonstrated that high expression levels of ECM1 inhibit transforming growth factor beta (TGFB) activation to prevent liver fibrosis (32). Lee et al investigated the functional role of ECM1 and concluded that it interacts with the epidermal growth factor (EGF) domain of various proteins, including HSPG2, and induce heparin-binding growth factor responses (33).…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, ECM-1 inhibits latent TGF-b1 activation during homeostasis preventing spontaneous fibrogenesis. In fact, ECM-1 supplementation can reverse fibrosis when ECM-1knockout mice are exposed to liver damage (86).…”
Section: Ecm Protein Association With Growth Factors Cytokines and mentioning
confidence: 99%
“…IL-6 and IL-21 induce ECM-1 expression, which is a positive regulator of TFH cell differentiation in humoral immunity, germinal centre formation and antigen-specific antibody production by antagonising IL-2 signaling (217). Fan et al described ECM-1 as a key mediator of liver tissue homeostasis (86). Depletion of ECM-1 severely affected liver architecture in mice, promoting liver fibrosis development, but without significant inflammation or hepatocyte damage (86).…”
Section: Ecm Proteins Which Drive Anti-inflammatory Immune Responses mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, TET3 was shown to upregulate the TGFB pathway genes TSP1 and TGFBR2, suggesting a positive feedback loop between TET3 and TGFB1 to promote HSC activation and hepatic fibrosis (Xu et al, 2020). In addition to TGFB signaling influencing HSC activation, hepatocyte produced extracellular matrix protein 1 (ECM1) has been shown to suppress TGFB levels and prevent HSC activation in an in vivo ECM1 knockout mouse model (Fan et al, 2019). Although TGFB remains a strong mediator of HSC activation and fibrogenesis, additional profibrogenic cytokines contribute to this process as well.…”
Section: Pro-fibrogenic Cytokines In Hsc Activation During Hepatic Fimentioning
confidence: 99%